The attenuated Pseudorabies virus vaccine Bartha K61 induces a weak cellular immunity: implications for the development of PRV-vectored vaccines - Xing, Gang; Li, Hui; Lu, Chenhe; Li, Haimin; Jin, Yulan; Yan, Yan; Shang, Shaobin; Zhou, Jiyong (Frontiers in Immunology, 2024)
Pseudorabies virus (PRV), causing Aujeszky’s disease in swine, has important economic impact on the pig industry in China and even poses a threat to public health. Although this disease has been controlled by vaccination with PRV live attenuated vaccines (LAVs), the potency of PRV LAVs in inducing cellular immunity has not been well characterized. In this study, using PRV Bartha K61 strain (BK61), the most-used PRV LAVs, as a model, we re-examined the cellular immune response elicited by the BK61 in mice and pigs by multicolor flow cytometry. We found that phenotypic activation of T cells, NK cells and B cells was hardly detected after vaccination. However, antigen-specific IFN-γ-producing CD4 T cells rather than CD8 T cells were dominantly detected but at low frequency upon restimulation with live BK61 virus. These BK61-specific CD4 T cells are also able to simultaneously produce TNF-α and IL-2, showing characteristics of multifunctional T cells. However, BK61-specific CD4 T cells showed weak secondary response upon challenge with PRV DX strain. Further vaccination with PRV-infected dendritic cells (DCs) transiently increased the percentage of IFN-γ-positive CD4 and CD8 T cells but eventually restored to low frequency and did not improve the protective efficacy of BK61 against challenge, suggesting that PRV BK61 induced a relatively weak cellular immunity that could not be overcome by the DC vaccination. Similar immune responses were also observed following vaccination with another PRV LAV HD/c in mice and pigs, suggesting that this may be an intrinsic drawback of PRV LAVs in inducing cellular immunity. Our results demonstrated that PRV LAVs elicited a CD4 Th1-biased weak cellular immunity which is implicative for the development of PRV-vectored vaccine.